ASENet 2016 WELL-RECEIVED BY STUDENTS OF ASEAN COUNTRIES - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, 21 January 2016 – The ASEAN Student Entrepreneurship Network (ASENet) 2016, organised by Universiti Sains Malaysia (USM) through the USM Students’ Representatives Council (MPPUSM) was well-received by participants from the ASEAN countries.